2017
DOI: 10.1111/1753-6405.12640
|View full text |Cite
|
Sign up to set email alerts
|

Using simulation modelling to examine the impact of venue lockout and last‐drink policies on drinking‐related harms and costs to licensees

Abstract: Objective: Many variations of venue lockout and last-drink policies have been introduced in attempts to reduce drinking-related harms. We estimate the public health gains and licensee costs of these policies using a computer simulated population of young adults engaging in heavy drinking. Method:Using an agent-based model we implemented 1 am/2 am/3 am venue lockouts in conjunction with last drinks zero/one/two hours later, or at current closing times. Outcomes included: the number of incidents of verbal aggres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The studies we identified conceptualized, described or modelled systems of interest to alcohol-harm prevention research primarily in the United States (n = 38) [22,23,29,, Australia (n = 17) [28,31,[77][78][79][80][81][82][83][84][85][86][87][88][89][90][91] and the United Kingdom (n = 7) [26,[92][93][94][95][96][97]. We also found examples of generic alcohol systems (n = 16) [24,93,[98][99][100][101][102][103][104][105][106][107][108][109][110][111], as well as examples from Sweden (n = 2) [112,113], South Africa (n = 2) [114,115], Canada (n = 1) [116], Denmark (n = 1)…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies we identified conceptualized, described or modelled systems of interest to alcohol-harm prevention research primarily in the United States (n = 38) [22,23,29,, Australia (n = 17) [28,31,[77][78][79][80][81][82][83][84][85][86][87][88][89][90][91] and the United Kingdom (n = 7) [26,[92][93][94][95][96][97]. We also found examples of generic alcohol systems (n = 16) [24,93,[98][99][100][101][102][103][104][105][106][107][108][109][110][111], as well as examples from Sweden (n = 2) [112,113], South Africa (n = 2) [114,115], Canada (n = 1) [116], Denmark (n = 1)…”
Section: Resultsmentioning
confidence: 99%
“…These refer to computational models which model non-linear causal relationships between system elements, which may operate at varying temporal and spatial scales in order to understand emergent patterns of system behaviour [22,31]. The majority of the dynamic simulations we identified described the process of developing, or developed, ABMs (n = 29) [28,31,[42][43][44][45][46]58,60,62,64,[74][75][76][77][78]81,83,84,[87][88][89][90]92,[96][97][98]107,119] or advocated for the use of, or developed, system dynamics (SD) models for alcohol-harm prevention (n = 9) [22,23,26,59,60,73,91,99,100]. ABMs model individual agents with different personal characteristics who interact with other agents according to 'rules' that govern their behaviour within a specific environment [42,83].…”
Section: Dynamic Simulation Modellingmentioning
confidence: 99%
See 3 more Smart Citations